Mixed arsonium-iodonium and sulfonium-iodonium ylides: synthesis and characteristics - Podrugina, Tatyana A.; Alferova, Vera A.; Mironov, Andrei V.; Matveeva, Elena D.; Gleiter, Rolf; Zefirov, Nikolay S. (Tetrahedron, 2016)
The preparation and properties of novel mixed arsonium-iodonium and sulfonium-iodonium ylides are reported. A series of substituted arsonium and sulfonium ylides was obtained by the nucleophilic substitution of iodonium groups in mixed ylides. A one-pot process, which included the nucleophilic substitution and silylation of arsonium-iodonium ylides with subsequent elimination of the silyl group and a Wittig olefination reaction, provided route to access Z-α,β-unsaturated haloketones.
Available online 14 September 2016
Gesehen am 02.11.2020